Do Students’ Career Aspirations Predict their Career Choices? A Qualitative Survey of Advanced Level Secondary School Students in Uganda - Ampaire, Anne; Kajumba , Mayanja M.; Muwagga , Anthony (African Journal of Education,Science and Technology (AJEST), 2021)
This article presents findings from a study on- “how students’ career aspirations predict their career choice at the advanced secondary level of education in Uganda”. This was premised on three predictors of career aspirations namely; financial remuneration, employment prospects and opportunity for professional growth. The study aimed at answering the question: Do Students’ Career Aspirations Predict their Career Choices? The study presents qualitative narratives from a survey of 48 male and female students randomly selected from 16 secondary schools in the Eastern and Northern regions of Uganda. The narratives were collected using an interview schedule. These were analyzed using a thematic strategy with inductive coding. The study findings showed that students peg their choices to career they perceive have stable progressive salaries for a decent life. They also look at occupations that will enable them have quick placements and finally career that will allow avenues for further training and robust skills. The results revealed that although most of the students’ career choices were based on the three predictors of career aspirations, other contributory factors including the student’s interest and ability were equally paramount. It was concluded that financial remuneration, future employment, and career growth were critical determinants of career choice at this level of education. It is recommended that education stakeholders should design holistic career support programs for students. These will enable students to access relevant career information, implied prerequisite skills, and the prevailing career path to enable them make appropriate career decisions at this level of education in Uganda.